2020
DOI: 10.1111/jace.17546
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring carboxyl tubular carbon nanofibers/MnO2 composites for high‐performance lithium‐ion battery anodes

Abstract: Three kinds of novel carboxyl modification tubular carbon nanofibers (CMTCFs) and MnO 2 composites materials (CMTCFs/MnO 2) are prepared by combining hypercrosslinking, liquid phase oxidation and hydrothermal technology. The complex morphology and crystal phase of MnO 2 in CMTCFs/MnO 2 are effectively regulated by adjusting the hydrothermal reaction time. The δ-MnO 2 nanosheet-wrapped CMTCFs (CMTCFs@MNS) are used as anode and compared with the other two CMTCFs/ MnO 2. Electrochemical analysis shows that CMTCFs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…44 MnO-CNF, 45 Zn 2 SnO 4 -CNT, 46 GeO 2 -CNF, 47 FeCO 3 -CNF. 48 TiO 2 -SnZnO-CNF, 49 MgFe 2 O 4 -CNF, 50 Mn 3 O 4 -CNT, 51,52 FeCO 3 -CNT, 53 NiCo 2 O 4 -CNT, 54 Fe 3 O 4 -CNF, 55 MnO 2 -CNF, 56 MnO 2 -CNT. 57 Further, several publications also reported the combination of 1D carbon nanostructures with a heteroatom (phosphor, nitrogen, and metal oxide phosphides/nitrides), i.e., N-CNF, 58,59 P-CNT.…”
Section: Theoretical Specific LImentioning
confidence: 99%
See 2 more Smart Citations
“…44 MnO-CNF, 45 Zn 2 SnO 4 -CNT, 46 GeO 2 -CNF, 47 FeCO 3 -CNF. 48 TiO 2 -SnZnO-CNF, 49 MgFe 2 O 4 -CNF, 50 Mn 3 O 4 -CNT, 51,52 FeCO 3 -CNT, 53 NiCo 2 O 4 -CNT, 54 Fe 3 O 4 -CNF, 55 MnO 2 -CNF, 56 MnO 2 -CNT. 57 Further, several publications also reported the combination of 1D carbon nanostructures with a heteroatom (phosphor, nitrogen, and metal oxide phosphides/nitrides), i.e., N-CNF, 58,59 P-CNT.…”
Section: Theoretical Specific LImentioning
confidence: 99%
“…4B. Huyan et al 56 reported that phenomena were normal in nanostructured metal oxide and affected by several mechanisms, i.e., reversible growth of gel-like film on the electrode, interface storage mechanism, and structural changes on the electrode during the cycle. Table I summarizes the performance of 1D carbon nanostructures composite as Li-ion battery anode.…”
Section: Theoretical Specific LImentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with conventional commercialized graphite anodes, transition metal oxides have caused a great deal of interest thanks to their high theoretical capacities and reliable discharging rates [ 6 , 7 , 8 , 9 , 10 , 11 ]. Among the various transition metal oxides, manganese oxide (MnO 2 ) is an attractive electrode candidate for LIBs due to its high storage capacity (1230 mAh g −1 ), rich abundance, and environmental friendliness [ 12 , 13 ]. However, the practical applications of MnO 2 -based anode materials are greatly limited by their poor intrinsic electric conductivity (~10 −7 –10 −8 S cm −1 ) and severe volume expansion and pulverization of MnO 2 matter from repeated charge/discharge cycles [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…MnO 2 is a well-known electrochemically active oxide that has been widely applied as an active material for the research fields of supercapacitors [39], electrocatalysis [40], and lithium-ion batteries [41]. Recently, the function of MnO 2 has extended to become a surface modification material on cathode materials, such as LiMn 2 O 4 [42], Li 3 V 2 (PO 4 ) 3 [43], and LiMn 0.333 Ni 0.333 Co 0.333 O 2 [44], in order to obtain a better electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%